Reconstituted Village: Relocating Traditional Houses and Transforming Traditional Malay Villages - Yung Ren Tan (Journal of Regional and City Planning, 2019)
In the current social and economic conditions, the preservation and conservation of historic buildings has become a challenge. The city of Kuala Terengganu dates as far back as the 17th century, however, the city currently has very few historical buildings. What is worse is that within the short period of the last 20 years, the town has lost almost half of its 200-year old Straits-Chinese shophouses. Architecturally significant traditional Malay houses are being torn down on a large scale to free up land on the fringes of the city. The loss of old villages that have always been a significant part of the town at this scale have raised awareness to start protecting some of the architecturally and historically important Malay houses and, in a wider context, some of the traditional villages. However, the increasing land value of the land where these villages sit on poses a great challenge. This paper discusses the idea of having a reconstituted village as a refuge to save traditional Malay houses from being demolished. Unlike brick and masonry based historical buildings, traditional Malay houses are sophisticated prefabricated houses and can be dismantled and reconstructed in a new location. This supports the idea of forming a reconstituted village with a collection of architecturally significant Malay houses. The idea of relocating these houses and putting them back in their original context could create a harmonious ambience. This process will eventually lead to an urbanized village that is a destination by itself. From an architecture enthusiast's perspective, such a village would be a last resort to protect these precious old houses from being demolished and at the same time contribute to the tourism sector. Recreating a collective village with real traditional Malay houses is a feasible option for the future of these villages and an approach of reinventing heritage tourism in the city.Abstrak. Dalam kondisi sosial dan ekonomi saat ini, preservasi dan konservasi bangunan bersejarah telah menjadi tantangan. Kota Kuala Terengganu berasal dari abad ke-17, namun kota ini saat ini memiliki sangat sedikit bangunan bersejarah. Yang lebih buruk adalah bahwa dalam kurun waktu singkat selama 20 tahun terakhir, kota ini telah kehilangan hampir setengah dari ruko Peranakan yang berusia 200 tahun. Rumah-rumah tradisional Melayu yang signifikan secara arsitektur dihancurkan secara besar-besaran untuk membebaskan tanah di pinggiran kota. Hilangnya desa-desa tua yang selalu menjadi bagian penting kota pada skala ini telah meningkatkan kesadaran untuk mulai melindungi beberapa rumah Melayu yang penting secara arsitektur dan historis, dan dalam konteks yang lebih luas, beberapa desa tradisional. Namun, meningkatnya nilai dari tanah di mana desa-desa ini berada merupakan tantangan besar. Makalah ini membahas gagasan pembangunan kembali desa sebagai tempat perlindungan untuk menyelamatkan rumah-rumah tradisional Melayu agar tidak dihancurkan. Tidak seperti bangunan bersejarah berbasis batu bata dan batu, rumah tradisional Melayu adalah rumah prefabrikasi yang canggih dan dapat dibongkar dan direkonstruksi di lokasi baru. Ini mendukung gagasan pembentukan desa yang dibangun kembali dengan koleksi rumah-rumah Melayu yang secara arsitektur penting. Gagasan merelokasi rumah-rumah ini dan mengembalikannya ke dalam konteks aslinya dapat menciptakan suasana yang harmonis. Proses ini pada akhirnya akan mengarah ke desa perkotaan yang merupakan tujuan dengan sendirinya. Dari sudut pandang pemerhati arsitektur, desa seperti itu akan menjadi pilihan terakhir untuk melindungi rumah-rumah tua yang berharga ini dari kehancuran dan pada saat yang sama berkontribusi pada sektor pariwisata. Menciptakan desa kolektif dengan rumah-rumah tradisional Melayu yang nyata adalah pilihan yang layak untuk masa depan desa-desa ini dan sebuah pendekatan untuk menciptakan kembali pariwisata warisan di kota.Kata kunci. Preservasi, desa, rumah tradisional, desa perkotaan.